Applications of Steel Slag Powder and Steel Slag Aggregate in Ultra-High Performance Concrete - Jin Liu (Advances in Civil Engineering, 2018)
The applications of steel slag powder and steel slag aggregate in ultra-high performance concrete (UHPC) were investigated by determining the fluidity, nonevaporable water content, and pore structure of paste and the compressive strength of concrete and by observing the morphologies of hardened paste and the concrete fracture surface. The results show that the fluidity of the paste containing steel slag is higher. The nonevaporable water content of the hardened paste containing steel slag powder is close to that of the control sample at late ages. Both steel slag powder and steel slag aggregate react and connect tightly to gels and hardened paste, respectively. When the cement replacement ratio is no more than 10%, the proportion of pores larger than 50 nm in the hardened paste containing steel slag powder is close to that of the control sample, and the UHPC containing steel slag powder can display satisfactory compressive strengths. The UHPC containing steel slag aggregate demonstrates higher compressive strengths.